Mathematical Modelling of the Fifth Law of Library Science - Yakubu, Hosea; Hosea, Hannatu; Inamete, Emem Ndah Happiness; Simeon, Taiwo Olusola (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
Over the years, most students see Mathematics as a chain of abstract ideology that has no application in real life. These beliefs tend to make the course more difficult to learn, as memorization and deduction seemed impossible. Mathematical modelling has increasingly become a valuable tool in different disciplines, library and information science inclusive. It helps to quantify and predict library operations, user behaviors, and resource utilization. The principles of library science have been foundational in shaping the organization, management, and accessibility of information. In 1931, Shiyali Ramamrita Ranganathan, an Indian mathematician and librarian, formulated five laws of library science that have since become cornerstones of modern library practice. Among these, is the Fifth Law of Library Science which states that; “The library is a growing organism” captures the dynamic, evolving nature of libraries as institutions that must adapt to changing societal, technological, and informational needs. This study focuses on the application of Mathematical modelling to the fifth law. The paper also discusses various mathematical frameworks, including differential equations and growth models that can be employed to simulate the continual development of libraries